2013
DOI: 10.1534/genetics.113.152256
|View full text |Cite
|
Sign up to set email alerts
|

Integration of New Genes into Cellular Networks, and Their Structural Maturation

Abstract: It has been recently discovered that new genes can originate de novo from noncoding DNA, and several biological traits including expression or sequence composition form a continuum from noncoding sequences to conserved genes. In this article, using yeast genes I test whether the integration of new genes into cellular networks and their structural maturation shows such a continuum by analyzing their changes with gene age. I show that 1) The number of regulatory, protein-protein, and genetic interactions increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
70
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(79 citation statements)
references
References 67 publications
9
70
0
Order By: Relevance
“…These observations seem to indicate that house-keeping genes emerged early in evolution and are older in age, knowing that they reflect more essential and constitutive functions. The idea that gene essentiality is associated with older genes has been reported in several studies, for example on yeast [14] and mammalian genes [16]. By contrast, the observations that human tissue-specific genes had emerged later in evolution may reveal that human specific cellular or physiological roles are implemented at molecular level by the appearance of newer genes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations seem to indicate that house-keeping genes emerged early in evolution and are older in age, knowing that they reflect more essential and constitutive functions. The idea that gene essentiality is associated with older genes has been reported in several studies, for example on yeast [14] and mammalian genes [16]. By contrast, the observations that human tissue-specific genes had emerged later in evolution may reveal that human specific cellular or physiological roles are implemented at molecular level by the appearance of newer genes.…”
Section: Resultsmentioning
confidence: 99%
“…Phylostratigraphy is the usual methodology applied to find the origin and emergence of genes [10, 11]. Previous phylogenetic studies showed that the evolutionary history of different coding parts of the genome have relations with diseases [12], codon usage [13], essentiality, interactions [14], stemness and self-renewal [15]. Other studies have shown that older genes evolve slower [16], encode longer proteins, present higher expression levels, possess higher intron density and are subject to stronger purifying selection [17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, these data support the proposed hypothesis from Carvunis et al (2012), summarized in Figure 1, for how de novo genes form. The Abrusán (2013) article is one study using fungal lineages. There are many other species with fully sequenced genomes and significant amounts of systems biology data.…”
Section: Genetic and Protein Interactionsmentioning
confidence: 99%
“…8. In this study, Abrusán (2013) was limited by the data that were available, which is only on annotated genes (i.e., previously identified genes). How might this limitation skew the findings on characteristics of proto-genes?…”
Section: Estimate Your Evolutionary Relatedness To the Cockroachmentioning
confidence: 99%
See 1 more Smart Citation